Determinants of Earnings Persistence in Property and Real Estate Sector Companies - Rusmawati, Zeni; Marina, Anna; Sya'ban, Ma'ruf (Politeknik Negeri Jember, 2025)
The current condition of the real estate property sector is fluctuating, depending on government stimulus, investors and public interest. Companies will survive and even thrive if they are able to maintain and secure future profits. This study examines whether operating cash flow, debt levels, accruals, sales volatility, and institutional ownership are factors that can affect earnings persistence. This study was conducted on real estate and property companies listed on the IDX for the 2020-2024 period totaling 78 companies with a total of 390 observations. This study uses agency theory and signal theory. The method used in this study is quantitative. The data analysis technique uses multiple linear regression processed with SPSS software. The results and conclusions of this study indicate that the factors that affect earnings persistence are operating cash flow, debt levels, accruals, sales volatility and institutional ownership have an influence on earnings persistence.